Dialogic Discussion as a Platform for Building Speaking and Vocabulary Skills - Ramos, Allan Paul S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study explored (1) the most common speaking and vocabulary problems of 12 senior high students; (2) the implementation of 3 ESL teachers of dialogic discussion to address the identified students’ problems; (3) the improvement of students; and (4) the insights and implications of the intervention. Using a qualitative mosaic approach, the study used field notes and conversations with students and teachers. During preliminary data collection, it was found that the students’ speaking and vocabulary problems comprised fluency and accuracy issues, language function deficiencies, negative affective state, and poor classroom atmosphere. To address these problems, the three teachers implemented five dialogic discussion sessions. The implementation characterizes structure, scaffolding, and socialization. For students, the sessions helped them increase their confidence and speaking skills. These findings suggest that dialogic discussion may function as a platform engendering processes such as agency, exploration, and enhancement. The study recommends actions for teachers and future researchers.